2022
DOI: 10.3390/beverages8030045
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Kombucha

Abstract: Kombucha is a fermented sweetened tea with a mixed fermenting culture of yeast and acetic acid bacteria. While the history of kombucha is not completely clear, it is now available around the world and has shown an increase in availability and demand in the United States market. The proponents of kombucha consumption tout the varied health benefits it can provide. The final kombucha flavor and composition is a function of both the initial tea used and the fermentation process. While the ascribed benefits are va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 82 publications
0
23
0
3
Order By: Relevance
“…The decrease in pH over the fermentation period indicated that the bacteria and yeasts in the kombucha SCOBY converted sugars into various organic acids, such as acetic acid, gluconic acid, glucuronic acid, lactic acid, and other secondary metabolites 79 . Furthermore, a low kombucha pH also limits the undesirable growth of microbial contaminants 4 . It should be noted that the final pH values of the kombucha products may be correlated with the different substances released from the raw materials or generated during fermentation, which may affect the microbial growth and metabolic activities of the kombucha SCOBY 79 .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in pH over the fermentation period indicated that the bacteria and yeasts in the kombucha SCOBY converted sugars into various organic acids, such as acetic acid, gluconic acid, glucuronic acid, lactic acid, and other secondary metabolites 79 . Furthermore, a low kombucha pH also limits the undesirable growth of microbial contaminants 4 . It should be noted that the final pH values of the kombucha products may be correlated with the different substances released from the raw materials or generated during fermentation, which may affect the microbial growth and metabolic activities of the kombucha SCOBY 79 .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have potential toxicological and health implications on the human body. Yet, the number of articles and reviews that discuss the concentration of Bas in kombucha is still limited [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…65 Bishop rightly says that 'faith essentially involves something actional'faith implies action or, better, a disposition to act. 66 However, it's not any old disposition to action that faith implies. When you put your faith in God, the action to which you are thereby disposed is not, say, coming through for God with respect to what God relies on you to do.…”
Section: Faith and Doubt: Pluralism About Faith's Positive Cognitive ...mentioning
confidence: 99%